Comparison Between Different Composite Resins Used for Clear Aligner Attachments: An In-Vitro Study - Gazzani, Francesca; Bellisario, Denise; Quadrini, Fabrizio; Parrinello, Francesca; Pavoni, Chiara; Cozza, Paola; Lione, Roberta (Frontiers in Materials, 2022)
Attachments are specific features of clear aligner treatment designed to ensure the aligners retention and the predictability of tooth movements. The properties of composite resin used for their reproduction play a relevant role to preserve their integrity and shape over the time. Thus, the aim of the present evaluation was to compare the mechanical properties and the wear performance of two nanocomposite by means of mechanical and tribological tests. Twelve samples for both flowable nanocomposite (FNC) and conventional nanocomposite (CNC) were created. The two nanocomposites differ in terms of filler volume and viscosity of the mixture. The following tests were performed: thermal analysis and burning test; flat instrumented indentation test and a compression stress relaxation test; tribological analysis. Wear evaluation was performed by means of a contact probe surface profiler and a TayMap software for the 3D analysis. A customized step-sliding test was conducted to simulate the clinical application of materials with a polymethyl methacrylate (PMMA) ball used as counterpart. Wear evaluation of both resin surfaces and PMMA ball was performed. No differences were found in terms of polymeric nature and quantity of nanoparticles in the matrix. FNC showed lower density values (1.62 g/cm3± 0.02) and inorganic percentage residue (41%) than the CNC (respectively 1.95 g/cm3± 0.01 and 23%). Significant differences in terms of decrement of stress values, elastic modulus’ (1114.12 ± 91.39 MPa) and stress relaxation rate (24.39%±3.23) were observed for the CNC when compared to the FNC (respectively, 835.04±184.73 MPa and 40.19% ± 4.65). FNC showed higher values of dynamic friction coefficient (0.72±0.017) and more worn and deeper profiles than the conventional ones. The step-sliding test with a PMMA ball confirmed a higher friction coefficient for FNC and a greater wear of the PMMA surfaces when used against flowable samples. Lower viscosity of FNC ensures a better adaptation during clinical attachment fabrication, whereas it has a negative impact on mechanical properties. CNC showed greater performance and resistance under mechanical stresses than the flowable ones resulting more suitable for the clinical needs.